2014
DOI: 10.1167/iovs.14-14893
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Adaptive Optics Imaging of the Temporal Raphe and Its Relationship to the Optic Disc and Fovea in the Human Retina

Abstract: The angle of the raphe in the study was not consistent with classic raphe models. While the angle showed relatively large individual variability, there seems to be a systematic relation between the disc, fovea, and raphe. It may be useful for individualizing retinal measurement strategies with regard to perimetry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
41
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 35 publications
4
41
0
Order By: Relevance
“…1 are subject to rotations of the head/eyes, but the angle formed by all 3 structures (disc-fovea-raphe) is not. In our 15 subjects this angle was 172.4 ± 2.3° (ranging from 168.5 to 176.2°), which agrees well with prior estimates [9,12,13]. …”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…1 are subject to rotations of the head/eyes, but the angle formed by all 3 structures (disc-fovea-raphe) is not. In our 15 subjects this angle was 172.4 ± 2.3° (ranging from 168.5 to 176.2°), which agrees well with prior estimates [9,12,13]. …”
Section: Resultssupporting
confidence: 89%
“…Both thickness [2,8,9] and intensity [11][12][13][14] of the RNFL have been used by other groups to estimate the orientation of the temporal raphe, and both are reasonable indicators since the apparent "missing" fibers at the raphe should reduce both thickness and intensity recorded by OCT at the level of the RNFL.…”
Section: Generation Of En Face Imagesmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2014, Chauhan et al 5 used spectral domain-OCT to show for a group of 15 eyes that there is considerable variability in the temporal raphe position, varying from approximately −4° to 12° relative to a strictly horizontal meridian. The temporal raphe has also been visualised in small numbers of eyes using adaptive optics 6. In this study, we evaluated the anatomical relation between the positions of the optic disc, fovea and temporal raphe using swept source OCT (SS-OCT, Atlantis, Topcon, Tokyo, Japan).…”
Section: Introductionmentioning
confidence: 99%
“…[37][38][39][40][41][42][43][44][45][46][47] Further, it has been recently shown that the RNF bundles can be imaged in controls and patients with glaucoma. [48][49][50][51][52] The purpose of this study was to use AO-SLO data to better understand the nature of local damage of the macula in glaucoma patients. We were particularly interested in the AO-SLO appearance of the RNF bundles in and around the transition from the relatively healthy to clearly abnormal (AB) regions, as it is a likely site of disease progression.…”
mentioning
confidence: 99%